ANALYSIS OF FACTORS AFFECTING CORN FARMING PRODUCTIVITY IN UJUNG TANAH VILLAGE, MARE SUBDISTRICT, BONE REGENCY - Juliana, Andi; Suradi, Adam Rahman; Halim, Hasriliandi (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
This study aims to determine the factors that influence corn farming productivity in Ujung Tanah Village Mare Sub-district Bone Regency. The variables examined in this study include labor, seeds, fertilizers, pesticides, capital, and land area.  The research was conducted from  March to April 2025 in Ujung Tanah, Mare Sub-district, Bone Regency. The factor used was a quantitative factor with a survey technique. Respondents were selected using Simple Random Sampling, with a total of 35 corn farmers. Data were collected  through questionnaires and analyzed using multiple  linear regression.The results showed that simultaneously, labor, seeds, fertilizers, pesticides, capital, and land area significantly affect corn farming  productivity. Partially, seeds and  fertilizers have a significant influence, while labor, pesticides, capital and land area do not significantly affect productivity. This means that the better the use of seeds and fertilizers by farmers, the higher the productivity of corn farming  will be.  Keywords: corn, factors production, farming, productivity